Classification and sequelae of arrested eruption of primary molars - INGER KJÃƒÆ’Ã¢â‚¬Â R (IAPD and Blackwell, 2008)
In a study of 1059 Swedish children, the prevalence of ankylosis of primary molars was found to be 8.9%, occurring most frequently in the mandible 1 . Different studies have indicated that there is a familial occurrence of ankylosis. This suggests that a genetic disposition is important in relation to ankylosis of primary molars 1 .